A new matrix converter modulation strategy maximizing the control range - Igney, Jens; et al. (2004)
This paper presents a new modulation strategy for matrix converters, which provides the maximum control range including reactive input power. The modulation strategy bases on modern representations of the switch state in the space vector domain. There, geometrical considerations lead to a comprehensible strategy to eliminate free variables without reducing the intrinsic control range of the switch matrix. A comparison with other modulation strategies shows, that this control range exceeds the control range of all previously proposed modulation strategies. A further advantage is, that low switching losses are expected, because a maximum of switches are idle during a modulation period.